Pengaruh Penggunaan Octane Booster Terhadap Konsumsi Bahan Bakar Kendaraan Roda Empat - Bachri, Karel Octavianus; Soewono, Arka Dwinanda; Satryanatha, Josaphat Febrian; Fortino, Antonius Edwin (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2023)
Due to increasing fuel prices, most people in Indonesia choose to use fuel with an octane rating of 90. However, using fuel with a lower Research Octane Rating or RON can affect the performance and efficiency of vehicle engines, especially if the compatibility between fuel octane and the engine's compression ratio is neglected. One solution to this problem is adding an octane booster to RON-90 gasoline to resemble gasoline with an octane rating of 92. The purpose of this research is to conduct an experimental study to see the effect of using a commercially available octane booster on the fuel consumption of a multi-purpose vehicle with an engine capacity of 1500 cc. Fuel consumption testing was performed using a road test based on the full-to-full method. The measurement results show that using an octane booster in RON -90 gasoline can reduce vehicle fuel consumption by 6.82%. However, the decrease in fuel consumption is still less compared to vehicles using RON-92 gasoline. Economic analysis found that using an octane booster in a motorcar could be a cost-efficient alternative to a more expensive RON-92 petrol.